2020
DOI: 10.1002/jmri.27334
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Flow Quantification in Great Vessels Using Motion‐Corrected Radial Phase Contrast MRI: Comparison With Cartesian

Abstract: BackgroundPhase contrast MRI in the great vessels is a potential clinical tool for managing fetal pathologies. One challenge is the uncontrollable fetal motion, potentially corrupting flow quantifications.PurposeTo demonstrate improvements in fetal blood flow quantification in great vessels using retrospectively motion‐corrected golden‐angle radial phase contrast MRI relative to Cartesian phase contrast MRI.Study TypeMethod comparison.Phantom/SubjectsComputer simulation. Seventeen pregnant volunteers.Field Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…When combined with phase contrast MRI, which quantifies velocity of moving fluids, accurate measurements of fetal blood flow are possible. One major obstacle to this imaging is the necessity of timing image acquisition with the cardiac cycle (47)(48)(49)(50)(51). Cardiac gating is used to time data acquisition with specific phases of the cardiac cycle, and MRI-compatible fetal ECG devices are now available (48,(51)(52)(53)(54)(55).…”
Section: Mri Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…When combined with phase contrast MRI, which quantifies velocity of moving fluids, accurate measurements of fetal blood flow are possible. One major obstacle to this imaging is the necessity of timing image acquisition with the cardiac cycle (47)(48)(49)(50)(51). Cardiac gating is used to time data acquisition with specific phases of the cardiac cycle, and MRI-compatible fetal ECG devices are now available (48,(51)(52)(53)(54)(55).…”
Section: Mri Techniquesmentioning
confidence: 99%
“…One major obstacle to this imaging is the necessity of timing image acquisition with the cardiac cycle (47)(48)(49)(50)(51). Cardiac gating is used to time data acquisition with specific phases of the cardiac cycle, and MRI-compatible fetal ECG devices are now available (48,(51)(52)(53)(54)(55). This technology has now been applied to fetal disease states including IUGR (54) as well as the fetus with cardiac malformations (38).…”
Section: Mri Techniquesmentioning
confidence: 99%
“…1). From then on, the following studies successfully demonstrated the feasibility of MOG for functional PC MRI in healthy and growth-restricted fetuses and fetuses with CHD at both 1.5 and 3 T [22,[47][48][49][50]. PC MRI applying MOG at 3 T revealed better inter-observer agreement, an increased SNR, and better visualization of small pulmonary vessels, compared to 1.5 T [22].…”
Section: Metric Optimized Gatingmentioning
confidence: 99%
“…PC MRI applying MOG at 3 T revealed better inter-observer agreement, an increased SNR, and better visualization of small pulmonary vessels, compared to 1.5 T [22]. Using MOG, flow evaluation of the great fetal vessels was successfully performed revealing the highest image quality for the descending aorta, but also smaller vessel hemodynamics (e. g., of the ductus arteriosus or peripheral pulmonary vessels) were quantified [22,47,50]. Phantom validation studies demonstrated sufficient reliability of MOG [48], and flow results were comparable to experimental studies in fetal lambs [47].…”
Section: Metric Optimized Gatingmentioning
confidence: 99%
See 1 more Smart Citation